Developing media of decorative buttons for students in creative fabrics course at fashion design program, state university of malang - Nafiah, Annisau; Kusumawardani, Hapsari; Sintawati, Esin; Annisha Rachman, Galuh; Nur, Emmalia (International Journal of Scientific Research and Management (IJSRM), 2022)
During a pandemic, online learning media is the primary tool in lectures. In light of this, lecturers in the Fashion Design study program at the State University of Malang needed to develop clear and inspirational media to support 60% of the practical course. The goal was to create two tutorial videos of round and square buttons to teach decorative buttons stitching in the Creative Fabrics course. These videos were expected to impart and provide new insights to increase students' creativity in making several forms of buttons using various decorative stitches methods as fashion decorations. The ADDIE model was utilized as the analysis tool. The validation result showed that the data was valid, complemented with the result from media expert of 80.4%, material expert of 83.3%, and feasibility study of 93%. The result showed that the videos were feasible and valid to be used as media for teaching and learning. The videos were considered easy to understand and encouraged students to implement the learning materials. The conclusion was that the tutorial videos were suitable for the Creative Fabrics course.